Analisis Kesantunan Berbahasa Presiden Ir. H. Joko Widodo pada Pidato Masalah Cabut Larangan Ekspor Minyak Goreng Kajian Pragmatik - Lestari, Tri (Medan Resource Center, 2023)
This research aims to explore language politeness in pragmatics related to the maxims of wisdom, generosity, respect, simplicity, consensus, and empathy. The data source for this study was a speech by President Ir. H. Joko Widodo on the lifting of the ban on cooking oil exports, obtained from YouTube. The research employed a descriptive method with a qualitative approach. The instrument used was documentary analysis. Data analysis involved careful listening, observation, comprehension of the speech content, data collection, observation, data analysis, addressing research questions, and drawing conclusions from the research findings. The results obtained were as follows: (a) 4 sentences related to the maxim of wisdom, (b) 2 sentences related to the maxim of generosity, (c) 1 sentence related to the maxim of respect, (d) 1 sentence related to the maxim of simplicity, (e) 1 sentence related to the maxim of consensus, and (f) 1 sentence related to the maxim of empathy.